Scrutinising the exceptionalism of young rural NEETs: A bibliometric review - Simões, F.; Erdogan, E; Muratovic, M.; Sik, D. (Youth and Society, 2022)
The situation of rural NEETs aged 15 to 24 remains understudied. However, transitions from adolescence to emerging adulthood are very demanding for those in the countryside. Our paper discusses this gap by characterising the scholarship focusing on rural NEETs. We undertook a bibliometric review based on 325 entries on Web of Science (WoS) using the Bibliometrix analysis package. Our approach included descriptive bibliometric analysis, co-citation networks assessment, and thematic analysis. Our findings show that the investigation efforts depicting younger rural NEET are recent and marginal in the larger context of international NEETs scholarship. The field is dominated by economy- and sociology-led networks. Concerns regarding health and employment issues are central in international publishing trends, showing a dominant youth-at-risk approach to this group. Still, themes associated with adolescent NEETs and relevant programs’ assessment are gaining traction. Our findings show a need for funding research initiatives to reduce the invisibility of young rural NEETs.